Supply Chain Resilience and Organizational Performance in the Nigerian Manufacturing Industry - Abiji, Abiji Emmanuel; Isienyi, Raluchukwu Andrew; Adebola, Agada Julius (Electronic Journal of Business and Management, 2026)
This study investigated the effect of supply chain resilience on organizational performance, particularly emphasizing supply chain agility, supply chain collaboration, and supply chain robustness. A survey research design was adopted to collect primary data from employees. The target population of this study consisted of 435 employees. Using the Krejcie and Morgan sample size determination table, the sample size obtained for the study was 205 respondents. Data were collected by means of a structured questionnaire, and a total of 200 usable responses were retrieved and used for analysis. Data were analyzed through descriptive statistics and multiple regression analysis, and the hypotheses were tested at 5% level of significance. The results revealed that supply chain agility has a positive and statistically significant effect on organizational performance, indicating that the firm’s ability to respond quickly and flexibly to changes enhances effectiveness. The findings further showed that supply chain collaboration has a significant influence on the performance of an organization, emphasizing information sharing, coordination, and strategic partnership in a supply chain. Moreover, supply chain robustness was also found to positively impact organizational performance, meaning the ability of the supply chain to absorb and resist disruption would lead to long-term performance. This study concludes that supply chain resilience is one major driver of manufacturing sector firms’ performance. In this regard, the study recommends that manufacturing firms should work on strengthening agile practices, developing collaborative supply chain relationships, and investing in robust supply chain structures to attain better performance and improved long-term sustainability.